Do Pharmacists Buy Bayer? Informed Shoppers and the Brand Premium * - Bronnenberg, Bart J.; Dubé, Jean-Pierre; Gentzkow, Matthew; Shapiro, Jesse M. (Quarterly Journal of Economics, 2015)
Abstract We estimate the effect of information and expertise on consumers’ willingness to pay for national brands in physically homogeneous product categories. In a detailed case study of headache remedies, we find that more informed or expert consumers are less likely to pay extra to buy national brands, with pharmacists choosing them over store brands only 9 percent of the time, compared to 26 percent of the time for the average consumer. In a similar case study of pantry staples such as salt and sugar, we show that chefs devote 12 percentage points less of their purchases to national brands than demographically similar nonchefs. We extend our analysis to cover 50 retail health categories and 241 food and drink categories. The results suggest that misinformation and related consumer mistakes explain a sizable share of the brand premium for health products, and a much smaller share for most food and drink products. We tie our estimates together using a stylized model of demand and pricing.